Zarządzanie w sektorze publicznym - od modelu tradycyjnego do governance - Wojciechowski, Eugeniusz (Management in Public Sector - from the Traditional Model to the Governance, 2007)
The content of the article is to outline process of modernization in public management starting from the traditional model up to the conception called governance. In systems of power and public administration all over the world very important changes take place in connection with globalization and development of communication technologies. Central and local governments face new challenges, therefore politicians and specialists in administration must act progressively according to new rules and solutions. The result of above mentioned are experiments and reforms leading to the reconstruction of public systems. The range of problems concerning public affairs quality management becomes target of researches since the 90's also from the economic point of view.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1161, s. 589-599